Riffat Hassan's Thoughts on Gender Issues in the Qur'an - Hakiki, Kiki Muhamad; Rohmatika, Ratu Vina (Faculty of Ushuluddin and Religious Study, Universitas Islam Negeri Raden Intan Lampung, 2024)
AbstractOne Muslim feminist figure who is not so sure about the interpretations of traditional interpreter is Riffat Hasan. In her works, she tries to reconstruct verses that have been interpreted with patriarchal bias, especially verses related to women. In her interpretation, Riffat Hasan offers four important points of her ideas. First, the theory of creation (An-Nisa: 1), (Al-'Araf: 189), (Az-Zumar: 6). This theme, according to her, is important to be reconstructed because the concept of equality and inequality comes from the concept of creation Second, the position of women (An-Nisa':34). According to him, in relation to position, the Qur'an does not distinguish between men and women. Third, regarding purdah (al-Ahzab verse 59). In interpreting these verses, Riffat Hassan takes three steps, namely (1) a normative-idealist and historical-empirical approach by reinterpreting the verses of the Qur'an, (2) deconstructing religious thought that (according to her) is gender biased, and (3) reconstructing religious thought that is not gender biased.Keywords: Deconstruction; Gender Issues; Riffat Hasan; Tafsir Al-Qur'an. AbstrakSalah satu tokoh feminis Muslim yang tidak begitu yakin dengan penafsiran para mufassir tradisional adalah Riffat Hasan. Dalam karya-karyanya, ia mencoba merekonstruksi ayat-ayat yang selama ini ditafsirkan dengan bias patriarki, terutama ayat-ayat yang berkaitan dengan perempuan. Dalam penafsirannya, Riffat Hasan menawarkan empat poin penting gagasannya. Pertama, teori penciptaan (An-Nisa: 1), (Al-'Araf: 189), (Az-Zumar:6). Tema ini menurutnya penting untuk direkonstruksi karena konsep kesetaraan dan ketidaksetaraan berasal dari konsep penciptaan Kedua, posisi perempuan (An-Nisa':34). Menurutnya, dalam kaitannya dengan kedudukan, al-Qur'an tidak membedakan antara laki-laki dan perempuan. Ketiga, mengenai purdah (al-Ahzab ayat 59). Dalam menafsirkan ayat-ayat tersebut, Riffat Hassan melakukan tiga langkah, yaitu (1) pendekatan normatif-idealis dan historis-empiris dengan cara melakukan penafsiran ulang atas ayat-ayat al-Qur’an, (2) melakukan dekonstruksi terhadap pemikiran keagamaan yang (menurutnya) bias gender, dan (3) melakukan rekonstruksi terhadap pemikiran keagamaan yang tidak bias gender. Kata Kunci: Dekontruksi; Isu Gender; Riffat Hassan; Tafsir Al-Qur’an.